How to: Design to include Indigenous Peoples and local communities - Larson, A.M.; Sarmiento Barletti, J.P. (CIFOR-ICRAF, 2023)
Indigenous Peoples (IPs) and local communities (LCs) often have a critical stake in decisions about land and resource governance. Historically, however, they have frequently been excluded from decision-making processes about the landscapes in which they live, including from discussions over the future and wellbeing of their ancestral territories and the resources located there (Palacios Llaque and Sarmiento Barletti, 2021; Rodriguez and Sarmiento Barletti, 2021).